Pengaruh Variasi Produk, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Toko Ramai Semarang - Adek Siti Ermawati; Sutopo Sutopo (Jurnal Ekonomi Manajemen Akuntansi, 2021)
This study aims to determine the effect of product variation on customer satisfaction in Toko Ramai Semarang, the effect of product quality on customer satisfaction in Toko Ramai Semarang, the effect of service quality on customer satisfaction in Toko Ramai Semarang, the influence of product variation, product quality, and service quality simultaneously affect satisfaction consumers of Toko Ramai Semarang. The type of research used is inferential. The population in this study are consumers who shop at TokoRamai Semarang. The sampling technique used the accidental sampling method with a total sample of 100 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression.